Muscle Quality and Structural Changes in Stroke Patients: An Ultrasonographic Evaluation - İlhan Celil Özbek; Özgür Akgül; Canan Tıkız; Zeliha Ünlü; Lale Cerrahoğlu (Türk Osteoporoz Dergisi)
Objective: The aim of this study is to evaluate muscle changes in stroke patients by assessing muscle diameter and muscle quality using ultrasonography. Materials and Methods: Forty male stroke patients and forty healthy male volunteers who fulfilled the predefined criteria were enrolled in the study. The patient group was evaluated with the Brunnstrom Lower Extremity Motor Evaluation, the Modified Ashworth Scale, the Functional Independence Measure, and the Functional Ambulation Scale. Diameter measurements of the quadriceps femoris muscle, were taken with B-mode ultrasonography, and shear wave elastography (SWE) values were recorded for both groups. Results: Stroke patients’ quadriceps femoris muscle diameter was significantly lower than that of controls (p<0.001), while SWE measurements exhibited no significant difference (p>0.05). Subgroup analysis based on stroke duration revealed lower diameter measurements in acute-subacute and chronic stroke patients compared to controls (both p<0.001), with no difference between stroke groups (p>0.05). Similarly, regardless of ambulation status, stroke patients had significantly lower quadriceps femoris muscle diameter than controls (p<0.001), with no disparity between ambulation groups (p>0.05). There was no significant difference in the groups’ SWE measurements (p>0.05). Conclusion: These results suggest a decrease in muscle thickness without deterioration in muscle quality. At this point, we believe that simultaneous evaluation with B-mode ultrasonography and elastography during ultrasonographic assessment of muscle changes will provide more objective results. This approach may help us more accurately understand the relationship between the quality and quantity of muscle tissue.